Beyond the call of duty: A Qualitative study into the experiences of family members acting as a Nearest Relative in Mental Health Act assessments. (29th January 2022) - Dixon, Jeremy; Stone, Kevin; Laing, Judy
Abstract: Research shows that tensions between family carers and professionals become acute where the issue of compulsory admission to hospital is at stake. In England and Wales, a specific family member is appointed to safeguard the interests of a person assessed under the Mental Health Act 1983. This currently occurs through the Nearest Relative (NR) role. The Government is proposing to replace this with a Nominated Person role, chosen by the service user. Drawing on the concept of carer burden, this study reports on the views of nineteen NRs in England to discover their experiences of being involved in a Mental Health Act assessment. Participants identified that they undertook the role due to a sense of duty. Their experiences were mixed with participants highlighting both feelings of distress during the assessment and feelings of relief once their relative had been detained. Participants reported feeling conflicted when their relative was detained and feelings of frustration towards mental health services. The findings have implications for proposals to reform the Mental Health Act 1983. They show that education and support programmes should be created for NRs/Nominated Persons and that research is needed to assess whether such support is effective at reducing carer burden. Abstract : Research shows that tensions occur between family carers and professionals when compulsory admission to hospital is being considered. In England and Wales, a specific family member is appointed to protect the rights of a person assessed under the Mental Health Act 1983 (which may lead to someone being detained in hospital against their will). This role is referred to as a Nearest Relative (NR). Our project used interviews to gain the experiences of nineteen NRs who had been involved in a Mental Health Act assessment. NRs told us that they took on the role due to a sense of duty. They had mixed experiences of Mental Health Act assessments. Some felt distressed by the experience whilst others felt relieved that their family member had been detained. Many were dissatisfied with the support which was offered by mental health services. The Government is proposing to replace NRs with a new Nominated Person role, which can be chosen by the service user. Our research identifies a need to provide training and support to those undertaking the new Nominated Person role. Research is also needed to assess whether such support is effective at reducing carer feelings of burden.